The Problems of Health Psychology and its Current Status - Hakobjanyan, Anna (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
Health problems can lead not only to physical and organic traumas, but can also do much harm to the person’s vital activity. Health can be examined as a multilevel system – on physical, psychological and social levels. The purpose of this article is the theoretical analysis of the phenomenon of health, illumination of the purposes, tasks, issues of experimental practice in health psychology as a young discipline and the analysis of existing problems of the discipline development in Armenia.
Keywords: health psychology, well-being, behavioral medicine, ill behavior, health behavior formation